Proceedings of the Mathematics, Informatics, Science, and Education International Conference (MISEIC 2019) 2019
DOI: 10.2991/miseic-19.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanogold and Nanosilver as Leprosy Drug Candidates and Their Activity Tests in Leprosy Patients; Case Study

Abstract: One of nanogold uses is as a leprosy drug because it has an activity to increase cell proliferation and collagen biosynthesis. These two activities are necessary for the process of recovery and closure of wounds, including in leprosy. Nanosilver can act as anti-bacterial material, including against leprosy bacteria Mycobacterium leprae. This study used a combination of nanogold and nanosilver to treat leprosy. The theoretical application was very suitable and promising optimal results. The question was whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…They feel the extraordinary in their joints. They feel much less pain and can rest in peace [19]. Medical record data in table 1 BT, BP and HR is the average data from 96 clinical trial volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…They feel the extraordinary in their joints. They feel much less pain and can rest in peace [19]. Medical record data in table 1 BT, BP and HR is the average data from 96 clinical trial volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Respondents were asked to consume health water products and drink regularly every day. The effects of Nanogold and Nanosilver have been tested and clinically proven safe for consumption because it is non-toxic [14].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Taufikuromah et al used a combination of gold and silver nanoparticles to topically treat epidermal wounds due to leprosy. They found that such a combination was effective in reducing the wound width by 80% in patients under the MDT regimen while the wound width of the control group had decreased only by 50% ( Table 3 ) [ 106 ]. However, the mode of action of these two nanoparticles towards the inhibition of growth and survival of Mycobacterium leprae (leprosy causing pathogen) is mostly unclear.…”
Section: Nanotechnology and Leprosymentioning
confidence: 99%